Let's get ready an experiential follow-through journey toolkit and multi-sensory safe space for children ages 4-7 to circumvent separation anxiety during school opening - Solas, Diego Stefano C.; Ilagan, Joy M. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Refusal behavior are often exhibited by preschool pupils during school opening. It is expected for a child to show signs of discomfort when being critically cut off from the source of protection since the children are only beginning to grasp the sense of the world that is why it is very important to take consider their behavior. Though it is considered normal as part of the child's nature and development, it has the potential to grapple onto a much greater distress if it has persisted to a certain extent. Most of the main caregivers pictured this phenomenon as if the child can simply disconnect their emotional bonds, which is one of the major source of distress that makes the first day of school traumatic.

This research aims to obstruct distress, ease the way to school, and positively reinforce children in establishing relationships through a visible output. The visual communicator has produced two creative solutions designed for dealing the aforesaid issue. The "Let's Get Ready" toolkit is an interactive play-based approach in establishing trust and environment familiarity. It contain various immersive components to help slowly ease the way to school in an enjoyable experience. For the second output, a multi-sensory safe space is produced specifically targeted for teachers of primary educational level. It is designed more than just a classroom decoration but rather a functionable place where th4 child can vent their complex emotions during distressed situations and help them regain self-composure.
Thesis (Bachelor of Fine Arts in Visual Communication)
Bibliography: leaves 232-240
Keywords: Separation anxiety in children -- Philippines -- Instructional and educational works; First day of school -- Philippines -- Instructional and educational works; Safe spaces